Experimental Demonstration of 16-QAM DD-SEFDM With Cascaded BPSK Iterative Detection - Jun Huang; Qi Sui; Zhaohui Li; Fei Ji (IEEE Photonics Journal, 2016)
To simplify the complexity of a spectrally efficient frequency-division multiplexing (SEFDM) system, cascaded binary-phase-shift-keying iterative detection (CBID) is proposed for square $M$ -ary quadrature-amplitude-modulation (M-QAM) SEFDM as the first decoding stage, in conjunction with a fixed sphere decoder (FSD). For 16-QAM SEFDM, the decoding complexity of FSD can be reduced to 1/4 with CBID-FSD replacing the iterative detection FSD algorithm to keep the same bit error rate. A 16∼20 Gb/s intensity-modulated single-sideband 16-QAM optical SEFDM is demonstrated by using the CBID-FSD algorithm.